Pengaruh Work Environment dan Quality of Work Life terhadap Work Productivity Generasi Z: Mental Health sebagai Variabel Mediasi - Rijaludin; Karsim; Mazayatul Mufrihah; Pramana Saputra (PT. PENERBIT TIGA MUTIARA, 2025)
This study investigates the influence of the work environment and quality of work life on individual work productivity among Generation Z, with mental health serving as a mediating variable within the structural model. Generation Z, as a demographic cohort increasingly dominating the labor force, exhibits distinctive psychosocial characteristics that necessitate adaptive managerial approaches, particularly concerning psychological well-being in the workplace. The sample comprised 161 respondents employed across various industrial sectors in Indonesia, selected using a sampling technique based on Lemeshow’s formula for populations lacking explicit definition. Data were analyzed using the Structural Equation Modeling (SEM) approach to assess causal relationships among constructs and to validate the proposed theoretical model. Empirical findings reveal that both the work environment and quality of work life exert a positive and statistically significant influence on mental health. Furthermore, these two variables also directly contribute to enhanced work productivity. In addition, mental health is demonstrated to be a significant mediator in the relationship between the independent variables and productivity, thereby reinforcing their indirect effects. These results underscore the importance of organizational policy formulation that strategically positions mental health as a core element in human resource management systems. Accordingly, well-being-based workplace interventions not only enhance productivity but also foster a sustainable work ecosystem for the current and future workforce.